Formulasi sediaan pasta gigi ekstrak etanol buah takokak (Solanum torvum Sw.) dan tulang ikan tuna sirip kuning (Thunnus albacares) terhadap bakteri Streptococcus viridans dan bakteri Escherichia coli - Hendri Faisal; Hanafis Sastra; Muhammad Andry; Melia Sari; Adek Chan; Muhammad Amin Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Takokak (Solanum torvum Sw.) is a traditional plant used as vegetables, fruits, ornamental plants and medicinal purposes. Takokak fruit contains secondary metabolites of alkaloids, flavonoids, saponins, tannins and steroids. Tuna fish bones are one of the biggest wastes from the tuna processing industry. Tuna fish bones contain minerals that are quite high compared to other parts of the body because the main elements of fish bones are calcium, phosphorus and carbonate. This study aims to make toothpaste preparations of ethanol extract of large chili fruit and yellowfin tuna bones and to determine the inhibition zone against Streptococcus viridans and Escherichia coli bacteria. This type of research is done experimentally. This type of research includes the manufacture of toothpaste preparations with concentrations of F1 (10%), F2 (15%), F3 (20%). Preparation evaluation included organoleptic test, homogeneity test, spreadability test, foam formation test, pH test, viscosity test, extrudability test and activity test for Streptococcus viridans and Escherichia coli bacteria. The results of the research were carried out to evaluate the physical preparations of toothpaste with ethanol extract of large chili fruit and yellow fin tuna bones, each toothpaste formulation met the organoleptic requirements, homogeneity, spreadability, foam formation, pH, viscosity and extrudability. Toothpaste preparations of ethanol extract of takokak fruit and yellow tuna bones have antibacterial effectiveness on Streptococcus viridans F1 (9.85 ± 0.32), F2 (11.85 ± 0.45), F3 (13.05 ± 0.34) and Escherichia coli F1 (3.15 ± 0.73), F2 (3.75±0.40), F3 (4.5±0.25). One way Anova data analysis showed a sig value of 0.00 <0.05 meaning that each concentration was significantly different, so that the results of the bacterial inhibition zone affected each concentration of toothpaste preparations.The conclusion of this study is that the ethanol extract of large chili fruit and yellow fin tuna bones can be formulated as a toothpaste preparation and effectively inhibits the growth of Streptococcus viridans and Escherichia coli bacteria in the weak, medium and strong categories.